(untitled) (Majalah Ilmiah UNIKOM, 2020)
The information system that is often used in higher education institutions is the Academic Information System which is used as Academic data processing by utilizing computer technology both in the form of ’hardware’ and ’software’. In this study the author uses the Webqual 4.0 method to carry out measurement of improvements, in service services. The Academic Information System is used as a proposal for improving the quality of information services, which is oriented towards student satisfaction. Measuring the level of user satisfaction can be done using the Webqual 4.0 method. This research is a survey research that uses a questionnaire to measure the satisfaction level of web site users according to the Webqual 4.0 model. The dimensions used in the preparation of the questionnaire consisted of information quality, service quality and user convenience. The questionnaire made was tested for validity and reliability, then distributed to 30 respondents. The method used to carry out data analysis was multiple linear regression analysis. The study / analysis conducted from 3 variables of webqual 4.0, the variable, namely the usability interaction, still has not provided a positive relationship with the user satisfaction variable (Satisfaction). Improvement efforts that must be made are increasing the interaction variable Usability (usability) in the Academic Information System of STMIK Amikom Surakarta. Key Words : survey research, webqual, usability interaction